A taxonomic assessment of novel and remarkable fungal species in Didymosphaeriaceae (Pleosporales, Dothideomycetes) from plant litter - Tennakoon, Danushka S.; Thambugala, Kasun M.; Silva, Nimali I. de; Suwannarach, Nakarin; Lumyong, Saisamorn (Frontiers in Microbiology, 2022)
Fungal taxonomy has a long history and changed significantly in the last few decades. Most recent studies have witnessed morphology combined with DNA-based molecular analyses as the main research tool for fungal species identification. During field surveys, some interesting Didymosphaeriaceae species were found from plant litter in China and Thailand. Morphology combined with phylogenetic analyses (Bayesian and maximum likelihood) of ITS, LSU, SSU, tef1-α, and tub2 loci was used to identify fungal taxa. In this article, three new species and six new host records are described. The new species, Montagnula acaciae, Paraconiothyrium zingiberacearum, and Paraphaeosphaeria brachiariae, can be distinguished from other species of the respective genera based on their distinct size differences (ascomata, asci, and ascospores) and DNA sequence data. The new host records, Montagnula jonesii, Paraconiothyrium fuckelii, Spegazzinia deightonii, and S. tessarthra are reported from Ficus benjamina, Dimocarpus longan, Hedychium coronarium, and Acacia auriculiformis respectively, for the first time. Also, Paraconiothyrium archidendri and P. brasiliense are reported for the first time from Magnolia sp. in China. Moreover, Paraconiothyrium rosae is synonymized under P. fuckelii based on close phylogeny affinities and morphological characteristics. In-depth morphological descriptions, micrographs, and phylogenetic trees are provided to show the placement of new taxa.